Kegel exercises with a guidebook for stress urinary incontinence treatment - Hakim, Surahman; Santoso, Budi Iman; Rahardjo, Harrina Erlianti; Setiati, Siti; Kusumaningsih, Widjajalaksmi; Prihartono, Joedo; Ibrahim, Nurhadi; Indriatmi, Wresti; Erwinanto (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Stress urinary incontinence (SUI) is uncontrollable urine leakage when intra-abdominal pressure increases. Behavioral therapy with Kegel exercise is currently the best conservative management recommendation for treating SUI patients. This study aimed to investigate the success of supervised Kegel exercises using the Kegel exercises guidebook in women with SUI. METHODS This quasi-experimental study involved both groups being taught the same regiment of Kegel exercises, but the intervention group was given the Kegel exercises guidebook. After 12 weeks, the compliance, subjective, and objective success rates were evaluated through the patient’s notes, Urinary Distress Inventory-6, Incontinence Impact Questionnaire-7, perineometer, and pad test. RESULTS Patients with a higher level of education had lower compliance to Kegel exercises (p = 0.01; odds ratio [OR] 0.38; 0.18–0.79). No significant difference was observed in the subjective symptom improvement between the two groups. The intervention group had a significantly higher success rate based on objective success by analyzing the 1-hour pad test results. The intervention group was also more adherent (p<0.001; OR 4.78; 2.51–9.0). CONCLUSIONS Patients who received the Kegel exercises guidebook were more compliant and more objectively successful than those who did not receive the manuals.